High prevalence of neuropathic pain in the hand of patients with traumatic brachial plexus injury: a cross-sectional study - Marcus V. B. Santana; Mauro T. Bina; Matheus G. Paz; Scheila N. Santos; Manoel J. Teixeira; Irina Raicher; José V. Martins; Daniel C. Araujo Andrade; Abrahão F. Baptista (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To describe the pain profile of patients with traumatic brachial plexus injury. Methods We enrolled 65 patients with traumatic brachial plexus injury. The Douleur Neuropathique 4 questionnaire was used to classify pain and the SF-36 was used to evaluate quality of life. Results The patients with traumatic brachial plexus injury were predominantly young male victims of motorcycle accidents. Pain was present in 75.4% of the individuals and 79% presented with neuropathic pain, mostly located in the hands (30.41%). The use of auxiliary devices (p = 0.05) and marital status (p = 0.03) were both independent predictors of pain. Pain also impacted negatively on the quality of life (p = 0.001). Conclusions Pain is frequent in patients with traumatic brachial plexus injury. Despite the peripheral nervous system injury, nociceptive pain is not unusual. Pain evaluation, including validated instruments, is essential to guide optimal clinical management of patients with the condition.